Marketing social para promocionar los derechos de los adultos mayores y personas con discapacidades, cantón El Empalme, año 2015. - Ureta Franco, Alexandra (2015)
This thesis entitled "" Social Marketing Plan to promote the rights of the elderly and especial capabilities people” took it place at the El Empalme town, province of Guayas, Ecuador, in 2015. The overall objective research was to design a social marketing plan to promote the rights of older adults and persons with limited capabilities in El Empalme. The problem that motivated the research was: How will it influence the social marketing campaign on the behavior of the members of the entities of goods and services (public and private companies) and on citizenship empalmeña, about the rights of adults elderly and persons with limited capabilities? The research found mainly that: only 14% of older and disabled adults in El Empalme owns the license of CONADIS. The 55% is not exempt from paying property taxes. 62% receive privileged attention on the tails of public and private sector. 43% feel that their right to a specialized public and private entities attention is respected. 76% never receive discounts on payment for electricity service, mobile and fixed internet. 93% do not have free access to a job. 54% feel very good use of the mass media, as a strategy to enforce the rights of the elderly and disabled. Strategies of Social Marketing-Mix were four types; Price (the set of communication tools aimed at promoting the rights of the elderly and disabled in El Empalme), Plaza (adopters of El Empalme town) Promotion (product distribution would be through ATL and Advertising BTL, PR, Social Media, Thematic marches, clubs Support and Strategic Partners) and advertising (advertising campaign consists of two stages, with the following means: Television, radio, posters, social networks and thematic marches the….